Latent iron deficiency in non-anemic children under five years of age - Riaz, Qurat ul Ain; Ahsan, Saima; Chaudhary, Tanveer Hussain; Soomro, Abdul Hafeez; Khan, Muhammad Sabir; Nazish, Shanza (Journal of Rawalpindi Medical College, 2023)
Background: The most common nutritional deficiency in world is iron deficiency. The iron deficiency is the most common cause of anemia due to nutritional deficiency and is seen most commonly in children under five years of age. Objective: To determine the frequency of iron deficiency in non-anemic children under five years of age. Methods: A descriptive cross-sectional survey was conducted in pediatrics department of –removed for blind review—from August 2020 to February 2021. A total of 145 non-anemic children, ages 2-59 months were enrolled through non-probability consecutive sampling in this study. The complete blood count and C-reactive protein were sent for laboratory tests to rule out infection/inflammation. In children with normal hematocrit (30-40%) and CRP (≤ 6), serum ferritin levels were sent. Those children in whom serum ferritin levels were ≤12ng/ml was regarded as cases of latent iron deficiency. SPSS version 23 was used for data entry and analysis. Age and gender for effect modifiers were controlled by stratification. The chi square test was used for post stratification. The value of p ≤ 0.05 was considered significant. Results: The mean age of the patients was 3.20±5.41 years. Among all children, 69 (47.6%) were boys and remaining 76 (52.4%) were girls. Out of 145 children, 62 (42.8%) were iron deficient whereas 83 (57.2%) were non-iron deficient. The male to female ratio of iron deficiency was 1:1.3. The prevalence of iron deficiency among infants was 46%, followed by toddlers 42% and preschoolers 41%. The mean serum ferritin level was 22.96±2.21 ng/ml. The mean hematocrit was 33.84±2.68. The statistical analysis showed that there was an insignificant association between iron deficiency and age groups of children (p ≥ 0.5). Conclusion: The study concluded that the iron deficiency in children is very common, especially in infants. Screening of iron deficiency in children under five years of age seems to be a very important task for better child care. Key words: Anemia, Iron-Deficiency; Child, Preschool; Malnutrition.